Database Floklore Dalam Undang-Undang Tentang Hak Cipta Dan Undang-Undang Tentang Pemajuan Kebudayaan - Sulistiorini, Lora Sinta (Jurnal Hukum & Pembangunan, 2022)
Law 28/2014 on Copyright and Law 5/2017 on Cultural Promotion have a major role in regulating and protecting floklore. This can be seen from the norms that regulate the mechanism for protecting floklore in Article 38 paragraph (2) of the Copyright Law, which states that the state is obliged to make an inventory, maintain, and maintain traditional cultural expressions.law a quo also regulates the procedures for recording as contained in Articles 66-72. Not only that, the Law for the Advancement of Culture also regulates the floklore database through Articles 16-26 of a quo. The two laws then raise the question, which law explicitly regulates floklore, especially the floklore database? Based on this explanation, this article will focus on two problem formulations, namely how to compare the floklore database in the Copyright Law and the Cultural Advancement Law, and which regulations (Copyright Law or Cultural Promotion Law) are appropriate to regulate the floklore database. By using a normative legal research method, which uses a statutory approach and a conceptual approach, this article will present a comparison of the provisions of the floklore database in the Copyright Law and the Cultural Promotion Law, as well as an analysis of whether or not the floklore database arrangement in the Copyright Law or the Cultural Promotion Law is appropriate. .database floklore in the Law for the Advancement of Culture is more detailed than in the Copyright Law. Second, floklore as one of the objects of cultural promotion in the Law for the Advancement of Culture, in some cases is also an object of IPR or in this case copyright in the Copyright Law.